Getting published in international journals: Perception of Indonesian scholars in linguistics and language education on the issues they face - Zifirdaus Adnan; Bambang Kaswanti Purwo (JOALL (Journal of Applied Linguistics and Literature), 2023)
Publishing research articles (RAs) in international journals (IJs) has been considered increasingly crucial by developing countries including Indonesia. For the Indonesian Government, publishing RAs in international journals is important to increase its competitive power academically as Indonesian universities are entering a global competition to attract students. Therefore, publishing RAs in international journals is becoming more and more important, e.g. for promotion, especially at senior levels. This study reports on the second and most widespread national-level survey of a three-year project funded by the former Indonesian Government through its Ministry of Research and Higher Education (MRHE). The central question is, "What are the key factors contributing to their lack of international research publications making the number low compared to smaller nations such as Thailand (before 2017)".This article reports the results of the second survey, with a much bigger population sample from many more universities located in many more different regions covering all the major islands in Indonesia compared to the first survey reported in our previous article. The bigger size of data is important based on the premise that the broader and the more diverse the information sources, the more comprehensive the information will be and the better understanding we gain. Some of the findings support the past results, but some contradict them.